2017
DOI: 10.1159/000452494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Liver Function in Patients Undergoing Partial Hepatectomy

Abstract: Background: Postresectional liver failure is the most frequent cause of fatal outcome following liver surgery. Diminished preoperative liver function in the elderly might contribute to this. Therefore, the aim of the present study was to evaluate preoperative liver function in patients <60 or >70 years of age scheduled for liver resection. Methods: All consecutive patients aged <60 or >70 years who are about to undergo elective liver surgery between 2011 and 2013 and underwent the methacetin breath liver funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
4
4
0
Order By: Relevance
“…Concerning liver function, median LiMAx values of our patient cohort were in the range of previous results . Our LiMAx values did not depend on the patients' age, which is in line with previous reports, showing that neither age nor sex influences the LiMAx outcome …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concerning liver function, median LiMAx values of our patient cohort were in the range of previous results . Our LiMAx values did not depend on the patients' age, which is in line with previous reports, showing that neither age nor sex influences the LiMAx outcome …”
Section: Discussionsupporting
confidence: 91%
“…11 Our LiMAx values did not depend on the patients' age, which is in line with previous reports, showing that neither age nor sex influences the LiMAx outcome. 11,25 Liver stiffness and function correlated significantly with the stage of fibrosis. THE and LiMAx were able to discriminate well between non-severe and severe fibrosis (AUROC: THE 0.94; LiMAx 0.89).…”
Section: Discussionmentioning
confidence: 96%
“…Perhaps we could not find a correlation between BMI and PHLF because the highest BMI was 33.7 in our series. Similar to previous studies, age is not a risk factor for hepatectomy [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…The decision for surgery was based on the 0.5% rule, and this patient underwent surgery and made an uneventful recovery. Furthermore, recent publications have reported that preoperative LiMAx values in general are signi cantly higher than postoperative LiMAx values [15,16,22,23]. Based on the measurements, changes in both directions were found.…”
Section: Discussionmentioning
confidence: 76%